200k views
13 votes
Evaluate (-4 + -3) – (2 – 7)

User Darbio
by
5.2k points

2 Answers

5 votes

Answer: -2

Explanation:

(-4+-3) -(2-7)

-7 - -5

-7+5= -2

User JMichaelTX
by
4.3k points
6 votes

Answer:

Explanation:

(-4) & (-3) have same sign ( -ve) . So add and put the (-) sign for the result.

2 is a positive number and (-7) is a negative number. Subtract and put the sign of the bigger number for the result.

(-4 + (-3) ) - (2 - 7) = -7 - (-5)

= - 7 + 5

= -2

User Paridokht
by
4.3k points